Demographic characteristics and Prevalence of Diseases: A case study of Chapagaun, Godavari Municipality, Lalitpur - Thapa, Raj Kumar; Karki, Tej Bahadur; Shahi, Arun; Thapa, Prakriti; Shrestha, Biswo (Nepal Journal of Multidisciplinary Research, 2020)
Sound health is the main property of each people so first priority should be given to the healthy life. Now, people are gradually becoming conscious about their health because of the various awareness program of Government and non-governmental agencies. Nepal is committed to access to quality health care for all its citizens. So, Government has encouraged the governmental and non-governmental sectors to provide the effective health service for hard to reach people living in the remote areas through different techniques. Health camp is one technique to provide the health service to remote people. The study was conducted among the 98 patients visited health camp organized in Chapagaun, Godavari Municipality, Lalitpur. The health camp had managed many health facilities: General checkup, screening of heart disease and cancer, orthopedic cases, Lab check in to creatinine, blood sugar, TFT, Vit D, Vit B 12 etc. The data was collected from the patient record file of health screening desk. The result shows that the female participation was higher than male attending the health camp for their health checkup. Similarly, age-wise, 41 to 60 years were more than other age group. It is interesting that the heath problem was similar between the male and female so statistically there was no significant association between the male and female regarding the prevalence of different types of diseases because the p value is .927 which is greater than .05 significant level. The further study can be done to identify the causative factors of increasing the risk of disease prevalence.